Analysis of knowledge and attitudes of the students of health and professional studies regarding the use of stimulative substances in sports - Stojanovic, Goran R; Vasiljevic Blagojevic, Milica; Bahtijari, Zulfer; Stankovic, Bratislav; Terzić Marković, Dragana; Stojanovic, Dusan G; Marinkovic, Valentina (Vojnosanitetski pregled, 2021)
Abstract Backrogund/Aim. Since the beginning of competitive sports, athletes have been trying to improve their abilities by taking various substances. The problem of using prohibited substances is not strictly tied to elite athletes; it is also present in the general population. The aim of this study was to test the knowledge and attitudes of the students regarding the use of stimulative substances and dietary supplements in sports. Methods. A cross-sectional study was performed among students at the College of Health and Professional Studies in Belgrade, Serbia. The data was collected by filling in an especially designed questionnaire. Results. Knowledge of prohibited substances and methods was characterized as “good” with 24.2% of respondents, namely 8.09% of males and 16.1% of females; knowledge of the adverse effects of prohibited substances and methods on health was demonstrated by 17.7% (9.03% of male respondents and 8.72% of female respondents). Conclusion. Student population is not knowledgeable enough about the problems of prohibited substances use and their negative effects on one’s health. The comparative analysis of our and European researches on knowledge, attitudes and uses of prohibited substances show a rather uniform prevalence rate. Not being aware of the adverse effects shows the need to further educate students.